2001
DOI: 10.1096/fj.00-0853fje
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of UBF is a critical determinant for rRNA synthesis and hypertrophic growth of cardiac myocytes

Abstract: Recent evidence suggests that increased translational efficiency of existing ribosomes alone is insufficient to account for the hypertrophic growth of cardiomyocytes and that synthesis of new functional ribosomes must occur. The rate-limiting step in ribosome accumulation is the transcription of the ribosomal 45S genes (rDNA) by RNA polymerase I. Our previous studies have demonstrated that increases in the expression of the rDNA transcription factor UBF correlated with hypertrophy of neonatal cardiomyocytes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…In yeast, it has recently been reported that the Tor signaling pathway regulates the Rrn3p-dependent recruitment of Pol I (60). Other studies have suggested various complementary scenarios affecting Pol I factors, further increasing the complexity and network of regulation, and these include regulated phosphorylation of UBF (51,56,(61)(62)(63), altered abundance of UBF (9,64,65), and the expression of an inhibitor of transcription (66).…”
Section: Pi3k Mtor and Mapk Coordinate Growth Factor Signaling To Pmentioning
confidence: 99%
“…In yeast, it has recently been reported that the Tor signaling pathway regulates the Rrn3p-dependent recruitment of Pol I (60). Other studies have suggested various complementary scenarios affecting Pol I factors, further increasing the complexity and network of regulation, and these include regulated phosphorylation of UBF (51,56,(61)(62)(63), altered abundance of UBF (9,64,65), and the expression of an inhibitor of transcription (66).…”
Section: Pi3k Mtor and Mapk Coordinate Growth Factor Signaling To Pmentioning
confidence: 99%
“…Thus, a constitutively active TIF-IA mutant accelerated proliferation by 43%, whereas dominant negative TIF-IA produced a 33% slowing (Zhao et al, 2003). Similarly, the hypertrophic growth of rat cardiac myocytes can be blocked by specifically preventing a 37% increase in rRNA synthesis (Brandenburger et al, 2001). The magnitude of these changes compares closely with the B40% suppression of rRNA synthesis exerted by endogenous RB and its relative p130 in embryonic fibroblasts, as determined with knockout mice (Ciarmatori et al, 2001).…”
Section: Pols I and Iii May Help Mediate The Growth Control Functionsmentioning
confidence: 74%
“…As described previously, contracting NCMs showed heightened expression of ANP and increased rDNA transcription (26,27). In experiments similar to those described above, INPP was overexpressed in arrested or contracting NCMs, and markers of ANP expression (ANP-luciferase) or rDNA transcription (pS-MECAT) were measured.…”
Section: Metabolism Of Ins(14)pmentioning
confidence: 57%
“…Transfection of CHO cells with pCR3.1-FLAG-INPP also increased INPP activity, which was measured as previously described (24) (Fig. 1A) (25)(26)(27). Control cells were contraction-arrested by the addition of 50 mM KCl to the medium to depolarize the cells.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation